A Perspective of Group Size on Children's Conditions for Wellbeing, Learning and Development in Preschool. Issue 5 (29th July 2019) - Williams, P.; Sheridan, S.; Pramling Samuelsson, I.
ABSTRACT: This study explores how group size influences children's conditions for wellbeing, learning and development in preschool in relation to the intentions in the revised (2010) Swedish preschool curriculum. The study is based on qualitative methods generated from interviews and open-ended questions in a questionnaire. Group size is dependent on three dimensions of preschool teacher's experiences of group size, constituted of various aspects: preschool teacher qualifications and competence, physical indoor and outdoor environment and the composition of the child group. The dimensions and aspects affect the critical number of children for it to function in a qualitative good manner. If these dimensions and aspects do not interact constructively, teachers and children experience the group as large.